Hemostatic Dysfunction Is Increased in Patients with Hepatosplenic Schistosomiasis Mansoni and Advanced Periportal Fibrosis - Leite, Luiz Arthur Calheiros (Public Library of Science, 2013)
BACKGROUND: Schistosomiasis mansoni is an endemic parasitic disease and a public health problem in Northeast Brazil. In some patients, hepatic abnormalities lead to periportal fibrosis and result in the most severe clinical form, hepatosplenic schistosomiasis. This study aimed to evaluate whether abnormal blood coagulation and liver function tests in patients with hepatosplenic schistosomiasis (n = 55) correlate with the severity of their periportal fibrosis. METHODOLOGY/PRINCIPAL FINDINGS: Blood samples were used for liver function tests, hemogram and prothrombin time (International Normalized Ratio, INR). The blood coagulation factors (II, VII, VIII, IX and X), protein C and antithrombin IIa (ATIIa), plasminogen activator inhibitor 1 (PAI-1) and D-dimer were measured by photometry or enzyme linked immunosorbent assay. Hyperfibrinolysis was defined on the basis of PAI-1 levels and a D-dimer concentration greater than a standard cut-off of 483 ng/mL. Standard liver function tests were all abnormal in the patient group compared to healthy controls (n = 29), including raised serum transaminases (p<0.001) and lower levels of albumin (p = 0.0156). Platelet counts were 50% lower in patients, while for coagulation factors there was a 40% increase in the INR (p<0.001) and reduced levels of Factor VII and protein C in patients compared to the controls (both p<0.001). Additionally, patients with more advanced fibrosis (n = 38) had lower levels of protein C compared to those with only central fibrosis (p = 0.0124). The concentration of plasma PAI-1 in patients was one-third that of the control group (p<0.001), and D-dimer levels 2.2 times higher (p<0.001) with 13 of the 55 patients having levels above the cut-off. CONCLUSION/SIGNIFICANCE: This study confirms that hemostatic abnormalities are associated with reduced liver function and increased liver fibrosis. Of note was the finding that a quarter of patients with hepatosplenic schistosomiasis and advanced periportal fibrosis have hyperfibrinolysis, as judged by excessive levels of D-dimer, which may predispose them to gastrointestinal bleeding.